2014
DOI: 10.1177/0003489414549154
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal Size Variability Is Associated With Sex

Abstract: Our data suggest that selection of ETT size in male patients should include height as a predictive factor. For female patients, it may be appropriate to select a uniformly smaller diameter ETT size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 25 publications
2
27
1
1
Order By: Relevance
“…The anterior-posterior (AP) tracheal diameter ranges between 1.27-2.38 cm for women and 1.68-2.86 cm for men [28]. Selecting the correct size ETT for patients is subjective and determined on the patient’s sex, height or weight [29]. The wrong size can cause tracheal ischemia (if too large) or facilitate aspiration (if too small) [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anterior-posterior (AP) tracheal diameter ranges between 1.27-2.38 cm for women and 1.68-2.86 cm for men [28]. Selecting the correct size ETT for patients is subjective and determined on the patient’s sex, height or weight [29]. The wrong size can cause tracheal ischemia (if too large) or facilitate aspiration (if too small) [29].…”
Section: Introductionmentioning
confidence: 99%
“…Selecting the correct size ETT for patients is subjective and determined on the patient’s sex, height or weight [29]. The wrong size can cause tracheal ischemia (if too large) or facilitate aspiration (if too small) [29]. A recent study identified an inverse relationship between tracheal size and body mass index [30], highlighting potential difficulties in making accurate assessments.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have utilized CT scans to evaluate the upper airway anatomy and its relevance to the demographic factors; however, these studies used MCM for CSA measurements [8-9, 15]. Since MCM assumes that the airways take a regular oval shape, we questioned the accuracy of such measurements based on the actual irregularity of the upper airway segments, the semi-triangular shape of the glottic and proximal subglottic areas, and the indentation of the posterior wall of the trachea with inspiration.…”
Section: Discussionmentioning
confidence: 99%
“…The anteroposterior diameter (APD) and transverse diameter (TD) are easily measured by any CT software. The cross-sectional area (CSA) is calculated mathematically from the APD and TD, assuming that the upper airway segments take an oval configuration [8-9]. The software calculation method (SCM) measures the CSA directly using the inbuilt software by drawing a perimeter manually around the area of interest and counting each pixel inside that area.…”
Section: Introductionmentioning
confidence: 99%
“…7.0–8.0 for men, while an I.D. 6.5–7.0 for women34. A multicenter study35 showed that 22.7% obese patients intubated with a tracheal tube >7.5 mm developed tracheal stenosis, compared with 3.3% of those with a tube size ≤7.5 mm, indicating the correlation between tube size and postintubation tracheal stenosis.…”
Section: Discussionmentioning
confidence: 99%